Analisis Teologi Inkulturasi Lukisan Perjamuan Kana dan Gerakan Sego Mubeng Gereja St Antonius Kotabaru Yogyakarta - Mahardika, Amadea Prajna Putra (Studia Philosophica et Theologica, 2024)
Inculturation in the context of religious life extends beyond mere adaptation in liturgical practices to permeate various aspects of human existence. This process involves the integration of cultural elements with spiritual values, fostering a harmonious unity between spirituality and everyday human reality. Two concrete examples of inculturation are explored: the Painting of the Wedding at Cana and the social movement of Sego Mubeng at St. Antonius Kotabaru Church, Yogyakarta. Through an in-depth analysis of these manifestations, the close relationship between art, daily life, and spirituality is highlighted. The painting serves as a medium to reflect religious values within the local cultural context, while Sego Mubeng demonstrates that inculturation extends beyond religious rituals into everyday activities, particularly in providing food assistance to those in need. This research enhances our understanding of how inculturation bridges the spiritual and earthly dimensions, as well as the complexity of its role in shaping worldviews and human behavior.